AB0044 Analysis of recombinant monoclonal antibodies from single B cells reveals early defects of B cell tolerance checkpoints in patients with sjÖgren's syndrome. (23rd January 2014) - Corsiero, E.; Sutcliffe, N.; Wardemann, H.; Pitzalis, C.; Bombardieri, M.
Abstract : Background: Sjögren's syndrome (SS) is an autoimmune disease characterized by high affinity circulating autoantibodies and characteristic B cell disturbances with a predominance of naïve and a reduction of memory B cells in the periphery. It is unknown at what stages of B cell differentiation tolerance checkpoints are defective in SS. Objectives: Here we aimed to determine the frequency of self-reactive and polyreactive B cells in the circulating naïve compartment of SS patients. Methods: Single IgD+CD27- naïve (and CD27+ memory) B cells were FACS sorted from 7 SS patients and RNA used to amplify Ig VH and VL genes which were then cloned and expressed as recombinant monoclonal antibodies displaying an identical specificity of the original B cells. B cells from healthy donors (HD) were used as control. Recombinant antibodies were tested towards different autoantigens to determine the frequency of autoreactive and polyreactive clones. Results: A total of 80 individual recombinant antibodies were generated from naïve and memory B cells of SS patients. Analysis of the VH and VL gene usage showed no significant differences between SS and HD. Preliminary data showed ANA reactivity but not polyreactivity in several peripheral naïve B cells from SS patients, suggesting an accumulation of autoreactive naive B cells in the periphery. Conclusions: Here using a novel strategy to express recombinant antibodies from single B cells we demonstrated an elevated frequency of autoreactive naïve B cells in the circulation of SS patients. This evidence likely reflects early defects in B cell tolerance checkpoints. References: Menard L, Samuels J, Ng YS, Meffre E. Inflammation-independent defective early B cell tolerance checkpoints in rheumatoid arthritis. Arthritis Rheum 2011;63:1237-1245. Tiller T, Meffre E, Yurasov S, Tsuiji M, Nussenzweig MC, Wardemann H. Efficient generation of monoclonal antibodies from single human B cells by single cell RT-PCR and expression vector cloning. J Immunol Methods 2008;329:112-124. Wardemann H, Yurasov S, Schaefer A, Young JW, Meffre E, Nussenzweig MC. Predominant autoantibody production by early human B cell precursors. Science 2003;301:1374-1377. Disclosure of Interest: None Declared